2021
DOI: 10.1039/d0qi01508c
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived room temperature phosphorescence of organic–inorganic hybrid systems

Abstract: Molecule-based crystalline materials with long-lived room temperature phosphorescence (RTP) have been paid tremendous attentions due to their promising properties for the critical requirements of applications in anti-counterfeiting, organic light-emitting diodes,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 62 publications
0
47
0
Order By: Relevance
“…1c), which is in favour of the separation of the molecular orbitals. 29 Extended along the bc plane, the DCPA linkers are tightly fixed between the rigid O-Cd-O 1D inorganic chains through coordination bonds, giving rise to a 3D porous structure (Fig. 1d).…”
Section: Resultsmentioning
confidence: 99%
“…1c), which is in favour of the separation of the molecular orbitals. 29 Extended along the bc plane, the DCPA linkers are tightly fixed between the rigid O-Cd-O 1D inorganic chains through coordination bonds, giving rise to a 3D porous structure (Fig. 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Organic RTP and long afterglow materials are expected to be widely used in optoelectronic and biochemical fields due to their long life luminescence, diversified design, and convenient preparation. [ 52,99,113–125 ] The above four hybrid RTP materials with micro/nanostructures have their own advantages and different application potentials. Because of relatively high RTP efficiency and tunable properties, OIHMs and MOFs can be used in advanced anticounterfeiting, information encryption, and optical devices.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 H diffusionordered spectroscopy (DOSY) NMR spectrum of 1 clearly indicated that these signals for the aromatic and Cp* units showed a single diffusion coefficient (2.38 × 10 −10 m 2 s −1 ), further confirming stable presence of structure 1 (Figure 3b). Moreover, the results of IR spectrum of complex 1 exhibits a strong band at 3441 cm −1 owing to the stretching vibration of the N-H bond of imidazole group [40][41][42], the peaks at 1030 and 1279 are likely the asymmetric and symmetric sulfonate stretches and the peaks at 1160 are due to CF 3 asymmetric and symmetric stretches [43][44][45]. The peaks at 1614 and 1444 are likely attributed to the vibration of aromatic ring structures of ligand L1 (Figure 4).…”
Section: Analysis Of Metallarectanglementioning
confidence: 97%